Peningkatan Kemampuan Penalaran dan Hasil Belajar Melalui Metode Pembelajaran Group Investigation(PTK pada Siswa Kelas X Multimedia B SMK Negeri 9 SurakartaSemester Genap Tahun Ajaran 2014/2015 ) - Pangestika, Ardha Wahyu, Prof. Dr. Budi Murtiyasa, M.Kom (2015)
Research purposes to improve the ability of reasoning and learning outcomes of students in solving mathematical problems through learning methods Group Investigation for class X Multimedia B SMK Negeri 9 Surakarta. his research is a class act that consisted of 3 cycles. Data collection methods used, namely, observation, field notes, and documentation. The results showed an increase in the ability of reasoning and student learning outcomes that can be seen from the indicators - indicators include: 1) Students submit ideas in the form of a mathematical sentence before the action of 0%, in the first cycle reached 9.68%, while the second cycle reaches 24.14 %, and after the third cycle the action of 40%, 2) students using the formula correctly before actions 29.03%, in the first cycle reaches 48.39%, while the second cycle reaches 65.52%, and after the third cycle the action of 80%, 3) The ability of the students perform arithmetic operations correctly before actions 29.03%, in the first cycle reaches 35.48%, while the second cycle reaches 58.62%, and after the third act cycle to 70%, 4) Value of students above the KKM ≥ 67 before action is 32.26%, in the first cycle reaches 64.52%, while the second cycle reaches 72.41%, and after the third cycle actions 83.33%. It can be concluded that the application of learning methods Group Investigation can improve reasoning skills and student learning outcomes.